(untitled) (ENTHYMEMA, 2023)
In this article we want to inquire and to compare the modalities through which Édouard Glissant and Salman Rushdie think and represent the world in their works. At first, we will study the two authors’ intellectual journeys. They are both characterized by the research of a “third space” in the transnational literary camp, free from the center-periphery dichotomy. Then we will place and contextualize their reflections in the debate on World Literature and Littérature-monde. Finally, we will compare their conceptions of realism, both characterized by a close relationship between the transcultural local (India and Antilles) and the creolized tout-monde.